LncRNA SOX2-OT/miR-30d-5p/PDK1 Regulates PD-L1 Checkpoint Through the mTOR Signaling Pathway to Promote Non-small Cell Lung Cancer Progression and Immune Escape - Chen, Zhoumiao; Chen, Zhao; Xu, Shaohua; Zhang, Qiang (Frontiers in Genetics, 2021)
Non-small cell lung cancer (NSCLC) is the most common type of lung cancer. Currently, treatment methods generally cause poor prognosis. Therefore, in order to seek new treatment options, we explored the internal mechanism of NSCLC. Firstly, the SOX2-OT/miR-30d-5p/PDK1 axis regulated by lncRNA SOX2-OT was predicted by bioinformatics methods, and the expression of SOX2-OT, miR-30d-5p and PDK1 mRNA in cells were detected by qRT-PCR while， PDK1 protein expression was detected by western blot. The results expressed that in NSCLC, SOX2-OT and PDK1 were notably overexpressed, and while miR-30d-5p was markedly underexpressed. The interaction between them was verified by dual-luciferase reporter and RNA binding protein immunoprecipitation assays. Subsequently, through CCK8, scratch healing, cell invasion and flow cytometry assays, we revealed that inhibiting the expression of SOX2-OT could inhibit the proliferation, migration and invasion of NSCLC cells and promote cell apoptosis; while simultaneous overexpression of PDK1 or inhibition of miR-30d-5p expression could reverse the inhibitory effect of SOX2-OT silence-mediated malignant progression of NSCLC cells. Then, the combined application of overexpressed PDK1 and rapamycin verified that PDK1 could regulate the expression of PD-L1 in NSCLC cells through the mTOR signaling pathway. Co-culture of CD8+ T cells verified that silencing SOX2-OT could inhibit the apoptosis of CD8+ T cells through miR-30d-5p/PDK1. Finally, tumor formation assay in animals confirmed that overexpression of SOX2-OT could promote the growth of NSCLC tumor in vivo. In this study, assays in vitro and in vivo were conducted to elucidate the mechanism by which SOX2-OT/miR-30d-5p/PDK1 drives PD-L1 through the mTOR signaling pathway to promote the malignant progression and immune escape of NSCLC. Keywords: non-small cell lung cancer (NSCLC); competing endogenous RNA (ceRNA); SOX2-OT; mTOR; PD-L1